A Unique Case of Sclerosing Mediastinal B Cell Lymphoma - Sethi, Neha; Kaul, Vijay; Pande, C L; Sharma, Anjali (Annals of Pathology and Laboratory Medicine, 2018)
Primary mediastinal B cell lymphoma is a rare subtype of diffuse large B cell Lymphoma (DLBCL) arising from putative thymic B cell origin. It accounts for 2-4 % of NHL. The present case was a 55 years old male presented with sudden onset of cough. Chest x ray and CT thorax showed presence of mildly enhancing solid mass in anterior mediastinum. Fine needle aspiration cytology (FNAC) from the mediastinal mass showed presence of poorly differentiated malignant neoplasm. Trucut biopsy from the same showed presence of tumour with foci of hyalinization. On immunohistochemistry tumour cells expressed CD20, CD 30 and CD 23. Hence the diagnosis of NHL of mediastinal sclerosing B cell type was made. The present case was one of the rare cases of Non Hodgkin Lymphoma (NHL) with an unusual presentation. Primary mediastinal B cell Lymphoma (PMBCL) with sclerosis is a distinct subtype of NHL with unique clinicopathological aspects and aggressive behavior. Prompt recognition and aggressive treatment may lead to relatively longer survival of patients.